Povidone iodine ‘WET’ technique: adenotonsillectomy in COVID era - Venkataramani, Nithya; Sachidananda, Ravi; Sachidananda, Nidhi R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
COVID-19 pandemic has significantly changed ENT practice. Most elective ENT (ear, nose, throat) surgeries possess a risk of infection, as well as potentially increasing complication.1 With the current pandemic slowly evolving and ever-increasing demand for elective services to restart, service delivery with minimal risk to healthcare workers is a challenge. ENT procedures like adenotonsillectomy, microdebrider FESS and mastoidectomy and many more are aerosol generating procedures. Adenotonsillectomy is particularly challenging with high risk to the operating room personnel as the viral load is significantly high in the nasopharynx and oropharynx. Evidence from China shows us that the pandemic could last for at least six months2 and modifications of techniques and adapting to the new norm is the key.